Social pedagogy in a human rights context: Lessons from primary schools in Iceland - Vilborg Jóhannsdóttir; Jóna G. Ingólfsdóttir (International Journal of Social Pedagogy, 2018)
The profession of social pedagogues (SPs) in Iceland provides services for a diverse group of people, particularly disabled people of all ages within variety of community settings with inclusive and rights-based practices as their primary professional responsibility. Social pedagogues (SPs) in Iceland have been part of the primary school professional community since the 1974 law on compulsory education opened up the schools for disabled children. This article is based on the school part of an ongoing study which focuses on the role, status and professional developmental needs of SPs in Iceland within their diverse work settings in light of the rights-based demands made by the CRPD. The aim of the school part is to explore, describe and interpret the views and understandings of SPs about the social pedagogue as a contributing actor within inclusive primary schools in Iceland. The data is derived from two main sources; the participants provided texts from a half-open questionnaire and focus group interviews. The analysis is performed with the help of the expansive learning theory within the cultural-historical activity theory framework (CHAT). The findings indicate a large mismatch between policy ideals, the SPs’ professional human-rights based values and the reality SPs face within inclusive schools. Thus, we argue that it is important to acknowledge and utilise the SPs professional expertise embedded in the human rights approach and their innovative practices as part of transformative expansive learning culture and collective change effort in accordance with Article 24 in the CRPD.